Children's Cognitive Reflection Predicts Conceptual Understanding in Science and Mathematics. (November 2020) - Young, Andrew G.; Shtulman, Andrew
The Cognitive Reflection Test (CRT) is a widely used measure of adults' propensity to engage in reflective analytic thought. The CRT is strongly predictive of many diverse psychological factors but unsuitable for use with developmental samples. Here, we examined a children's CRT, the CRT–Developmental (CRT–D), and investigated its predictive utility in the domains of science and mathematics. School-age children ( N = 152) completed the CRT–D, measures of executive functioning, measures of rational thinking, and measures of vitalist-biology and mathematical-equivalence concepts. CRT–D performance predicted conceptual understanding in both domains after we adjusted for children's age, executive functioning, and rational thinking. These findings suggest that cognitive reflection supports conceptual knowledge in early science and mathematics and, moreover, demonstrate the theoretical and practical importance of children's cognitive reflection. The CRT–D will allow researchers to investigate the development, malleability, and consequences of children's cognitive reflection.